The impact of Greenfield investment on domestic entrepreneurship - Tung Son Ha; Vu Tuan Chu; Nguyen Mai Tuyet Thi; Nguyen Dung Hoai Thi; Nguyen Anh Ngoc Thi (Journal of Innovation and Entrepreneurship, 2021)
The FDI-entrepreneurship nexus has received growing attention over the last decade. However, the empirical findings on their relationship have been inconsistent at best. This study seeks to examine how the inflows of Greenfield investment influence entrepreneurship of the host country. Using panel data from 110 countries during the period 2001-2018, we find that growing level of Greenfield investment brings detrimental impact on the level of total and opportunity-driven entrepreneurial activities in the host countries while the impact on necessity-driven entrepreneurship have been mixed. The results regarding the impact of Greenfield investment on total entrepreneurial activities and opportunity-based entrepreneurial activities are robust across different econometric settings, different time span, and different categories of control variables.
Keywords: 650; Entrepreneurial activities; Foreign direct investment; Greenfield investment; Opportunity-based entrepreneurship